Policy Implementation to Prevent and Control the Covid-19 by BPBD of Minahasa Regency - Sevry Maringka; Lexie A. Lumingkewas; Steven Vleike Tarore (Journal of The Community Development in Asia, 2021)
Based on the Implementation of the Covid-19 Prevention and Control Policy by the Minahasa Regency BPBD, the policy implementation model is more directed to the Public Policy Implementation Model proposed by Grindle. Policies have clear objectives as a form of policy value orientation. The objectives of policy implementation are formulated into specific action programs and projects that are designed and financed. The program is implemented according to plan. The implementation of a policy or program is – broadly speaking – influenced by the content and the context of implementation. Overall the policy implementation is evaluated by measuring program outcomes based on policy objectives. The results of this qualitative study prove that the legal basis is binding on policies in the prevention and control of Covid-19 BPBD Minahasa Regency.